Effect of floodplain trees on apparent friction coefficient in straight compound channels - A. P. Kozioł; A. Kiczko; M. Krukowski; E. Kubrak; J. Kubrak; G. Majewski; A. Brandyk (Hydrology and Earth System Sciences)
The interaction of water streams in channels with a complex cross section, involving the exchange of water mass and momentum between slowly flowing water in the floodplains and fast water in the main channel, significantly depends on the diversification of the surface roughness between the main channel and floodplains. Additionally, trees increase flow resistance strongly in floodplains and significantly in the main channel by intensifying the interaction process. As a result, the water velocity and the discharge capacity of both parts of the channel decrease and, at the same time, affect the flow conditions in the main channel. The results of laboratory experiments were used to determine the effect of floodplain trees on the discharge capacity of the channel with diversified roughness. The reduction in the velocity of the main channel caused by the stream interactions is described with the apparent friction coefficients introduced at the boundary between the main channel and the floodplain. The values of resistance coefficients and their changes as a result of the significant influence of trees on the interaction process were determined for different surface roughnesses of the main-channel bottom.